Systematics of the section Virescentia of the genus Batrachospermum (Batrachospermales, Rhodophyta) in Brazil - Agostinho, Douglas de Castro [UNESP]; Necchi Júnior, Orlando [UNESP] (My University, 2014)
This study evaluated the species level taxonomy and phylogenetic relationships among species of the section Virescentia of the genus Batrachospermum focusing on specimens from Brazil and other regions of the world. Molecular data (sequences of the plastid-encoded RuBisCO large-subunit gene, rbcL; and the barcode region of the mitochondrial encoded cytochrome c oxidase subunit 1, cox1) were generated, and morphological characters described for 13 populations. Molecular analyses of rbcL sequences revealed the existence of three well-supported clades with evident biogeographic trends, containing sequences of specimens of either North America (USA), Asia (Japan) or Brazil. Similarly, analysis of cox1 sequences (slightly different taxon sampling) also revealed three clades, containing specimens of either North America (USA), Europe (Norway) or Brazil. The three species recognized from Brazil in a previous study based on morphological data (Batrachospermum helminthosum, B. sirodotii and B. vogesiacum) could not be distinguished by molecular or morphological data. A new species was proposed for Brazilian specimens based on molecular and morphological evidence. Batrachospermum viride-brasiliense differed from the European species of the section Virescentia (B. bruziense, B. coerulescens, B. elegans, B. sirodotii and B. vogesiacum) by the longer carpogonia ( 40 lm) and larger carposporophytes ( 200 lm in diameter and 100 lm high) and carposporangia ( 19 lm long and 10 lm in diameter).
Keywords: Batrachospermales; Batrachospermum; Batrachospermum viride-brasiliense; Brazil; cox1; rbcL; Virescentia